PENGEMBANGAN BUKU GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS iNARASI PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGRI 106836 LIMAU MANIS - Intan Mutiah; Beta Rapita Silalahi (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2021)
This research is based on the problem found in SD Negeri 106836 Limau Manis, namely the absence of media in learning narrative writing skills. And make it difficult for students to express their ideas and ideas. The purpose of this study was to determine the improvement of narrative writing skills of fourth grade students of SD Negeri 106836 Limau Manis after using a series of picture books. This type of research is Research and Development (R&D) using the ADDIE model which has 5 stages but only uses 3 stages. The stages in research and development are Analysis, Design, and Development. The product validation stage was validated by 2 validators, namely 1 material expert and 1 media expert. The results of the validation on the picture book series about writing narratives by media experts scored 4.23 in the very good category, and the validation results by material experts obtained a score of 4.76 in the very good category. And obtained the average score of the two hali 4.50 in the very good category. It was concluded that the series of picture books to improve narrative writing skills in Indonesian class IV subjects at SD Negeri 106836 Limau Manis which was developed was suitable to be used as a learning medium.